PEMBINAAN KECAKAPAN HIDUP DAN KOMPETENSI ANGGOTA PRAMUKA PENEGAK DAN PRAMUKA PANDEGA - Tazqiatun Nisa Putri; Kayla Salsabilah; Mahdini Dalimunthe (CV. Arsy Persada Quality, 2024)
This research aims to determine the socialization of the scout symbol. This research uses descriptive qualitative research, documentation methods. The Scout Work Unit or abbreviated as Saka is a forum for developing interests and talents for members of the Penegak and Pandega ages. In this case, Saka Bahari is a forum for coaching in the marine and water sector so that swimming ability becomes the main asset for its members. In reality, several members have not yet fulfilled their swimming skills, so swimming training has become one of Saka Bahari's routine activities in particular. The purpose of this research is to determine the supporting factors of members of the Saka Bahari Maritime Scout Work Unit